Transmission of influenza reflects seasonality of wild birds across the annual cycle. (21st June 2016) - Hill, Nichola J.; Ma, Eric J.; Meixell, Brandt W.; Lindberg, Mark S.; Boyce, Walter M.; Runstadler, Jonathan A.
Abstract: Influenza A Viruses (IAV) in nature must overcome shifting transmission barriers caused by the mobility of their primary host, migratory wild birds, that change throughout the annual cycle. Using a phylogenetic network of viral sequences from North American wild birds (2008–2011) we demonstrate a shift from intraspecific to interspecific transmission that along with reassortment, allows IAV to achieve viral flow across successive seasons from summer to winter. Our study supports amplification of IAV during summer breeding seeded by overwintering virus persisting locally and virus introduced from a wide range of latitudes. As birds migrate from breeding sites to lower latitudes, they become involved in transmission networks with greater connectivity to other bird species, with interspecies transmission of reassortant viruses peaking during the winter. We propose that switching transmission dynamics may be a critical strategy for pathogens that infect mobile hosts inhabiting regions with strong seasonality.